2010
DOI: 10.4314/njps.v24i2.52908
|View full text |Cite
|
Sign up to set email alerts
|

Bile secretion in albino rat following chronic honey intake

Abstract: Summary:This study was carried out to evaluate the effect of honey intake on bile secretion, bile electrolytes, bilirubin and cholesterol levels including plasma cholesterol in albino rats. 20 male albino rats (200-210g) were used in the study. The rats were assigned randomly into 2 groups (control and honey-fed groups), each group containing 10 rats. The control was fed on normal rat feed and water while the test group was fed on normal rat feed with honey added to its drinking water (1ml of honey to every in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…This may result in non-alcoholic fatty liver disease or in other unpleasant conditions harmful to health if abused. Alagwu et al (2009) had earlier stated that chronic consumption of unprocessed Nigerian honey resulted in decreased bile flow, increased bile cholesterol and decreased plasma cholesterol in albino rats.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in non-alcoholic fatty liver disease or in other unpleasant conditions harmful to health if abused. Alagwu et al (2009) had earlier stated that chronic consumption of unprocessed Nigerian honey resulted in decreased bile flow, increased bile cholesterol and decreased plasma cholesterol in albino rats.…”
Section: Discussionmentioning
confidence: 99%
“…Honey is good but must be used with caution, especially in its application in poultry production. In literature, it has been reported that there were infiltrations of fat cells in the liver tissue of rats which was dosage-dependent (Avwioro et al 2012), decreased bile flow, increased bile cholesterol, and decreased plasma cholesterol (Alagwu et al 2009) in Albino rats and hypertrophy of follicle, giving it a deformed shape instead of the usual round shape in laying chickens (Abioja and Adekunle 2018). The authors concluded that chronic consumption of honey may increase the risk of hepatic damage.…”
Section: Use Of Honey and Other Natural Phytochemicalsmentioning
confidence: 99%
“…Honey also affects the HDL, LDL, VLDL, and total cholesterol, thus reducing the risk of heart disease. An animal trial showed a decrease in serum LDL and an increase in HDL, VLDL, and TG in comparison with Honey Composition, Therapeutic Potential and Authentication through Novel Technologies:… DOI: http://dx.doi.org/10.5772/intechopen.110007 the control, concluding that the honey can improve lipid profile and decrease the cardiac disease risk (Figure 1) [43].…”
Section: Cardioprotective Effect Of Honeymentioning
confidence: 99%